Kawasan Resort Hutan Mangrove dengan Pendekatan Arsitektur Ekologi di Kabupaten Sinjai - Sulaeha, Sulaeha; Burhanuddin, Burhanuddin; A'raaf Tauhid, Fahmyddin (TIMPALAJA : Architecture Student Journals, 2022)
Abstract_ One of the needs of modern society today is recreation. It is evidenced by the increasing number of tourists yearly, both foreign and domestic tourists. This increasing trend needs to be responded with an increase in the provision of accommodation to cover the activities of tourists. Therefore, it is necessary to have a place or means to relax the mind or refresh that is comfortable for the community in the form of a resort. South Sulawesi is one of Indonesia's provinces rich in natural and cultural potential. One of them is Sinjai Regency which has various possibilities ranging from marine tourism, historical sites, and other natural beauty that can be a characteristic and attraction for tourists. The object of this design is a resort located in the Tongke-Tongke mangrove forest area. Hence, one of the efforts to minimize environmental damage is to design environmentally friendly buildings. Ecological architecture is an ecologically sound development that utilizes natural potential as much as possible. The ecological architectural approach applied in the area is processing gray water, using local materials, and maximizing the green regions of the site. Keywords : Resorts; Ecological Architecture; Mangroves; Sinjai Regency.